Gambaran Faktor Penyebab Balita Stunting di Kampung Parakan Honje Sukamaju Kaler Kecamatan Indihiang Kota Tasikmalaya Tahun 2023 - Wikayah, Rahmadina; Sulistyoningsih, Hariyani (Universitas Galuh, 2023)
Preliminary studies at the Indihiang Health Center show an increase in stunting in the Indihiang sub-district. This study aims to describe the factors causing stunting in toddlers in Kp Parakanhonje Sukamaju Kaler, Indihiang District, Tasikmalaya City in 2023. The Quantitative Descriptive research method was conducted on 16 stunted toddlers with questionnaires as instruments. The results of data analysis showed that the majority of respondents graduated from high school (43.8%), had economic status < Rp2,533,341 (87.5%), did not receive exclusive breastfeeding (50%), had ARI disease (25%), did CPTS regularly (62.5%), incomplete immunization (25%), poor parenting (81.3%), and sufficient maternal knowledge (68.8%). The research recommendations involve regular weight monitoring, toddler weighing, health checks, and the adoption of a healthy lifestyle. Understanding and counseling to parents need to be improved to reduce the factors that cause stunting in toddlers.